If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 2x + 6 Reorder the terms: 1 + 4x = 2x + 6 Reorder the terms: 1 + 4x = 6 + 2x Solving 1 + 4x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 4x + -2x = 6 + 2x + -2x Combine like terms: 4x + -2x = 2x 1 + 2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 2x = 6 + 0 1 + 2x = 6 Add '-1' to each side of the equation. 1 + -1 + 2x = 6 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 6 + -1 2x = 6 + -1 Combine like terms: 6 + -1 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5
| 10j=100 | | 4(m+5)+6=7(m+3)-8m | | 65=4b+5 | | 4x-6=10x+10 | | 4x-9=3-(x-2) | | 18k+27= | | 2x-7+3x=11+x+2 | | 4(3c-2)=9c-7 | | 5-3(2d+5)=2 | | 6d+5=11 | | .6666667q-2=.3333333q+7 | | y+25=40 | | (3x+10)+(7x-30)=180 | | 9-8.2= | | 9(2k+3)= | | 5x+4(3x-16)=140 | | -6x+40=-3x-11 | | 0.5x^2*x^2=0 | | 2x+8=4x-128 | | 6x^2-x+13=0 | | 47=w-8 | | 5p-17=2(-2p-7) | | 2[7-6(1-n)]+9n=-20+4[6(n+1)-3n] | | 4(x+6)=35 | | -10x-3(9-x)=4(-2+5)-12 | | 2(x+1)=38 | | 24-5m= | | 2[7-6(1-n)]+8n=-14+3[6(n+1)-3n] | | 0.5x*x=0 | | 6+3-x/2=1 | | -77-14y-2y=-13 | | (2-x)(12+4x)=(-4-2x)(24-2x) |